The Effectiveness of PBL Based E-LKPD to Improve High School Students'Scientific Literacy on Global Warming Material - SILVIA YULLIANI (Department of Physics Universitas Negeri Padang, 2025)
This research attempts to analyze the efficiency of E-LKPD founded on the Problem Based Learning (PBL) model to enhance the scientific literacy of the high school pupils on global warming material. This kind of study is quantitative in nature study with a one group pretest-posttest pre-experimental approach. The sample of the research was 25 students of grade X phase E.2 of SMAN 1 X Koto Diatas who were selected using This is a purposeful sampling approach. The research instrument consisted of essay-based questions to assess scientific literacy.The data analysis methodologies employed were N-gain statistical test, normality test and effect size. The effect size technique to measure the effectiveness E-LKPD based on PBL can increase scientific literacy. Based on the study’s findings, shows that there is an average distinction before and after the implementation of E-LKPD founded on PBL. Students in the medium category obtained an increase in scientific literacy with a N-gain value of 0.56. Meanwhile, the effect size value obtained a value of 0.62 in the high category. Thus, E-LKPD based on PBL is efficient in enhancing the scientific literacy of pupils in high school on global warming material at SMAN 1 X Koto Diatas.